2014
DOI: 10.1177/1457496914552343
|View full text |Cite
|
Sign up to set email alerts
|

Operative Results of Periprosthetic Fractures of The Distal Femur In A Single Academic Unit

Abstract: Post-operative surgical site complications were relatively common in these mainly elderly female patients. The survival percentages of the re-arthroplasty and laminofixation groups were similar. The use of strut grafts in association with plating may decrease re-operation rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…Kurowicki et al (37) treated a series of 7 humeral PF (type B according to Wright and Cofield classification) using a locking plate with eccentrically placed screw holes; they reported a 100% union rate and excellent pain relief (mean visual analogic score of 0.5) at an average follow-up of 29 weeks. In Type B2 fractures the implant is loose but bone stock is preserved, and revision surgery is the preferred treatment choice (27,(38)(39)(40)(41) …”
Section: Classification Management and Resultsmentioning
confidence: 99%
“…Kurowicki et al (37) treated a series of 7 humeral PF (type B according to Wright and Cofield classification) using a locking plate with eccentrically placed screw holes; they reported a 100% union rate and excellent pain relief (mean visual analogic score of 0.5) at an average follow-up of 29 weeks. In Type B2 fractures the implant is loose but bone stock is preserved, and revision surgery is the preferred treatment choice (27,(38)(39)(40)(41) …”
Section: Classification Management and Resultsmentioning
confidence: 99%
“…Periprosthetic fractures are major complications and mostly require a challenging operative treatment with high post‐operative complication rates including, e.g., infections, non‐union and early loosening, resulting in the need for further revision surgery (Herrera et al., ; Leino et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, TKA can cause various complications such as aseptic loosening, infection, and periprosthetic fractures that are particularly in elderly patients. [8][9][10] More importantly, El-Galaly et al 11 has found that previous fractures in the distal femur and/or proximal tibia can increase the risk of early and medium-term revision of TKAs inserted, and the revision due to instability occurred more frequently in TKAs performed as a result of previous fractures. New retrograde nails have developed to increase stability, and biomechanical cadaveric studies showed that they even had a better performance in terms of fatigue resistance in younger patients, however, in elderly individuals with poor bone quality, it's unsuccessful because such patients have reduced bone volumes and weaker bones as well as joint distortion due to arthritis, in the condition their bones offer little purchase to nails.…”
Section: Discussionmentioning
confidence: 99%